Dengue Virus Ribonucleic Acid Detection Rates in Blood Donors Correlate With Local Infection Incidences During a Dengue Outbreak in Taiwan - Chen, Yun-Yuan; Lu, Chi-Te; Tsai, Mei-Hua; Yang, Cheng-Fen; Shu, Pei-Yun; Wu, Chia-Wen; Chen, Jen-Wei; Hung, Chi-Ming; Wei, Sheng-Tang; Hou, Sheng-Mou; Chen, Pei-Jer (The Journal of infectious diseases, 2022)
Abstract Background Evidence for mitigation of transfusion-transmitted dengue informed by surveillance data is lacking. In this study, we evaluated the risk of positive dengue viral (DENV) ribonucleic acid (RNA) from blood transfusions during a large outbreak in Taiwan. Methods Serum collected from blood donors living in districts experiencing the dengue epidemic were tested for DENV RNA using a qualitative transcription-mediated nucleic acid amplification assay (TMA). The TMA-reactive specimens were further tested for immunoglobulin (Ig)M and IgG antibodies, nonstructural protein 1 (NS1) antigen, and viral RNA by reverse-transcription polymerase chain reaction. We estimated DENV RNA prevalence and the number of DENV infections among blood donors. Results A total of 4976 specimens were tested for DENV RNA, and 21 were TMA-reactive. The detection rate was 0.84 (95% confidence interval [CI], 0.15–4.73), 3.36 (95% CI, 1.31–8.60), and 6.19 (95% CI, 3.14–12.17) per 1000 donors in districts where the weekly dengue incidence was 5–50, 50–200, and 200 or more per 100 000 residents, respectively. Alanine aminotransferase screening only detected 4.4% of TMA-reactive donations. A total of 143 transfusion-transmitted DENV infections probably occurred during this outbreak, accounting for 9.2 in 10 000 dengue infections. Conclusions Approximately 0.5%–1% of blood donations were DENV RNA positive in epidemic districts. The correlation of DENV RNA rates with dengue incidence may inform the design of effective control measures. We demonstrate the prevalence of DENV RNA as detected by the TMA platform among blood donors, which increased with rising local incidence in a nonendemic country. Our results will help facilitate mitigation polices and active surveillance during a serious outbreak.